Generalized Jones matrix optical coherence tomography: performance and local birefringence imaging - 安野 嘉晃; Makita Shuichi; Yamanari Masahiro; Yasuno Yoshiaki (Optics Express, 2010)
Phase retardation imaging including local birefringence imaging of biological tissues is described by generalized Jones-matrix optical coherence tomography. The polarization properties of a local tissue can be obtained from two Jones matrices that are measured by backscattered lights from the front and back boundaries of the local tissue. The error in the phase retardation measurement due to background noise is analyzed theoretically, numerically, and experimentally. The minimum detectable phase retardation is estimated from numerical simulations. The theoretical analysis suggests that the measurements with two orthogonal input polarization states have the lowest retardation error. Local birefringence imaging is applied to the human anterior eye chamber and skin in vivo.